2005
DOI: 10.1016/j.cell.2005.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Pore Formation by the Bacterial Toxin Pneumolysin

Abstract: The bacterial toxin pneumolysin is released as a soluble monomer that kills target cells by assembling into large oligomeric rings and forming pores in cholesterol-containing membranes. Using cryo-EM and image processing, we have determined the structures of membrane-surface bound (prepore) and inserted-pore oligomer forms, providing a direct observation of the conformational transition into the pore form of a cholesterol-dependent cytolysin. In the pore structure, the domains of the monomer separate and doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
437
4
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(485 citation statements)
references
References 38 publications
36
437
4
3
Order By: Relevance
“…The mechanism of pore formation by proteins of the CDC family involves a series of complex events including recognition and binding to the target membrane, the formation of pre-pore complexes on the membrane (oligomerization), and insertion of a transmembrane bbarrel (Heuck et al, 2003;Ramachandran et al, 2004;Tilley et al, 2005). Recently, it was reported that rapid denaturation of LLO was triggered at neutral pH by the premature unfolding of domain 3 transmembrane b-hairpins from the normal transmembrane b-barrel form (Schuerch et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of pore formation by proteins of the CDC family involves a series of complex events including recognition and binding to the target membrane, the formation of pre-pore complexes on the membrane (oligomerization), and insertion of a transmembrane bbarrel (Heuck et al, 2003;Ramachandran et al, 2004;Tilley et al, 2005). Recently, it was reported that rapid denaturation of LLO was triggered at neutral pH by the premature unfolding of domain 3 transmembrane b-hairpins from the normal transmembrane b-barrel form (Schuerch et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This correlates reasonably with the 'growing pore' model 46 where the toxin binds and immediately inserts the membrane to form small pores, which successively grow to full-size pores. Whether LLO also forms complete prepore rings, as in the case of pneumolysin 7 and PFO 47 remains to be shown experimentally, for example, by locking LLO in a prepore form like PFO 47 . However, at sublytic toxin concentrations (o500 ng ml À 1 ), we see no structures on the ghosts in our EM analysis that could be correlated with Ca 2 þ influx.…”
Section: Discussionmentioning
confidence: 99%
“…CDC monomers are secreted by the pathogenic bacteria in a water-soluble form that binds to a receptor on the target cell, where they oligomerize into a ring of up to 50 monomers with a diameter of around 300 Å 4,5 . Pore formation occurs through a subsequent conformational change, in which two helix bundles in each monomer convert into a pair of amphiphilic transmembrane b-hairpins that insert into the membrane 3,6,7 .…”
mentioning
confidence: 99%
“…Other than capsule, the most studied virulence factor of pneumococcus is pneumolysin, a toxin belonging to the family of bacterial cholesterol-dependent cytolysin. It causes direct cell damage by binding to the cholesterol in the host cell membrane followed by polymerization into 30-50 mers, thereby forming pores in the host cell membranes [124,197]. In addition to forming pores, it initiates immune-derived damage by activating complement system and induces inflammation [145].…”
Section: Bacterial Invasion and Cytotoxic Effectsmentioning
confidence: 99%